Practicality of an Inquiry-Based Module on Atomic Structure and Nanomaterials to Enhance Relational Understanding in Vocational High School Students - Siregar, Rabiyatul; Ubaidah; Huda, Zulmiftah; Romadon; Lubis, Armansyah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the practicality of an inquiry-based laboratory module on atomic structure and nanomaterials to enhance vocational high school students’ relational understanding, as outlined in the SOLO Taxonomy. The method employed is Research and Development (R&D) using the ADDIE model, which involves needs analysis, design, development, limited trials, and module evaluation by students and teachers of Agrobusiness and Horticulture at SMK Negeri 2 Banjit. Practicality data were obtained through a Likert-scale questionnaire assessing ease of use, student engagement, alignment with the SOLO Taxonomy, as well as the evaluation and impact of learning. The practicality test results show that all aspects of the module were rated as very practical, with average scores of 98.0% from teachers and 89.13% from students, indicating the module’s strong feasibility for classroom implementation in vocational chemistry learning. The integration of inquiry-based learning with the SOLO Taxonomy demonstrates meaningful pedagogical value in supporting students’ progression toward relational-level conceptual understanding and strengthening active engagement with abstract chemical concepts such as nanomaterials. Scientifically, this research contributes an empirically validated instructional model that bridges theory and laboratory practice, offering a scalable approach to enhancing higher-order thinking skills and practical competence in vocational science education. The findings underscore the importance of structured inquiry modules as a strategic approach to enhance the relevance and effectiveness of chemistry learning, thereby preparing students for industrial and professional demands.